Do beliefs about causation influence attitudes to mental illness? (2006)
Studies indicate that stigmatizing attitudes to mental illness are rampant in the community worldwide. It is unclear whether views about the causation of mental disorders identify persons with more negative attitudes. Using data collected as part of a community study of knowledge of and attitudes to mental illness in Nigeria, we examined the relationships between views about causation and attitudes. Persons holding exclusively biopsychosocial views of causation were not different from those holding exclusively religious-magical views in regard to socio-demographic attributes, and the two groups were not very dissimilar when general knowledge of the nature of mental illness was compared. However, religious-magical views of causation were more associated with negative and stigmatizing attitudes to the mentally ill. Findings demonstrate the challenge of developing and delivering an educational program to change public attitudes to mental illness.